The U-Turn in Government Facilitation: How Dutch Water Authorities Facilitate Nongovernmental Initiatives. (October 2019) - Grotenbreg, Sanne
Public authorities in infrastructure, aiming to facilitate societal initiatives, explore new forms of collaboration with nongovernmental actors. A comparative case study of two Dutch initiatives is conducted: energy generation at a public dam and the realization of a nature reserve. It is analyzed how and why the authorities' strategy regarding their nongovernmental partners changes over time. Authorities' strategy change is modeled on two axes: governmental investments and governmental influence, and a differentiation is made between limited facilitation, invitational facilitation, partnering, and Design, Build, Finance, Maintain, and Operate. A U-turn-shaped pattern in authorities' strategy is found: Authorities move from partnering to limited facilitation and subsequently revert to invitational facilitation. Institutional factors, process factors, and initiative characteristics are identified that explain the strategy changes. It is concluded that government facilitation is a dynamic, interactive process and that authorities adapt their strategy to the initiative at hand and are pragmatic in their approach.